Influence of Traditional Indonesian Values and Local Culture on Teaching Practices and Student Engagement: A Comparative Study of Rural and Urban Schools - Rahmiwati; Dwi Sulisworo; Dody Hartanto (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2026)
A school culture that supports collaboration, inclusivity, and openness to change can increase student engagement, teaching effectiveness, and academic achievement. Conversely, a more rigid or non-change-supporting culture tends to limit teachers' ability to implement learning innovations. The purpose of this study is to review recent research that highlights the influence of local cultural values ​​on teaching practices and student engagement in school. This research has gone through a process of identification, screening, eligibility, and inclusion through journals obtained from ERIC, Springer, and ScienceDirect. In reporting this research, the keywords used are "Traditional Value and Local Culture." The main findings from these studies underscore the importance of flexibility in teaching approaches that can appreciate cultural diversity to create more effective and meaningful learning experiences.